Epistolary heritage of Saint Nicholas as a source of history Orthodoxy in Japan of the Meĳi era - Zaruba Elizaveta (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Active study of the epistolary heritage of St. Nicholas of Japan began only in 2000, when there were published 2 collections of letters of the Archbishop («I’m here all alone Russian» and «Visible will of God to enlighten Japan»), which became a good addition to a separate pre-revolutionary publications of the letters of this Church ﬁgure. With rare exception, the original letters have survived and are in collections of the RSHA, DM of RNB, RDM RSL and RSALA (in personal funds of recipients and funds of the Holy governing Synod). While until now this material has not been investigated in its totality, was not made an attempt to characterize its informative value for a variety of issues of Church history and the history of the Orthodox mission in Japan. In the present work attempts a comprehensive analysis and classiﬁcation of 70 Epistles of Saint. The author proposes to divide the studied set of letters to the following semantic groups: letters to spiritual patrons and superiors, letters to fellow missionaries, as well as the letters of the Saint to the secular correspondents. The range of topics covered by Archbishop Nicholas in the Epistles, is extremely wide. Archbishop tells about the ﬁnancial situation of the mission, raises the question of the occurrence of indigenous Japanese people in the clergy of the Orthodox Church, informed his interlocutors about the spread of Christianity and the response of the Japanese society for the development of Orthodoxy in this country. information contained in these letters makes this source an invaluable addition to the oﬃ cial records, and one of the most important sources on the history of Japanese Orthodoxy of the Meĳ i era.